Recent Advances in Fluoroalkylation Strategies: Exploring Novel Reactivities and Synthetic Applications of Sulfone- and Sulfinate-Based Reagents for Mono-, Di-, and Trifluoromethylations - Knieb, Alexander; Prakash, G. K. Surya (Synthesis, 2024)
Fluoroalkylation serves as a pivotal strategy for chemists to precisely alter the properties of small molecules. Among the established fluoroalkylation protocols, sulfone and sulfinate reagents stand out as versatile tools for these reactions, particularly in mono-, di-, and trifluoromethylations. Their versatility lies in offering multiple pathways, encompassing electrophilic, nucleophilic, as well as radical mechanisms, thus providing diverse routes for controlled molecular modifications through a variety of very exciting mechanistic paths.1 Introduction2 Monofluoromethylation Strategies2.1 Fluorobis(phenylsulfonyl)methane (FBSM)2.2 2-Fluoro-1,3-benzodithiole-1,1,3,3-tetraoxide (FBDT)2.3 Benzothiazole-SO2CH2F, NaSO2CH2F, and ClSO2CH2F2.4 PhSO2CH2F3 Difluoromethylation Strategies3.1 PhSO2CF2H3.2 Benzothiazole-SO2CF2H3.3 2-PyrSO2CF2H3.4 NaSO2CF2H4 Trifluoromethylation Strategies4.1 PhSO2CF34.2 2-PyrSO2CF34.3 Benzothiazole-SO2CF34.4 NaSO2CF34.4.1 Electrochemical Approaches4.4.2 Photochemical Approaches4.4.3 Other Noteworthy Approaches5 Conclusion
Keywords: fluoroalkylation; sulfone; sulfinate; monofluoromethylation; difluoromethylation; trifluoromethylation